2008
DOI: 10.1189/jlb.1207810
|View full text |Cite
|
Sign up to set email alerts
|

Human monocytes/macrophages are a target ofNeisseria meningitidis Adhesin A(NadA)

Abstract: Specific surface proteins of Neisseria meningitidis have been proposed to stimulate leukocytes during tissue invasion and septic shock. In this study, we demonstrate that the adhesin N. meningitidis Adhesin A (NadA) involved in the colonization of the respiratory epithelium by hypervirulent N. meningitidis B strains also binds to and activates human monocytes/macrophages. Expression of NadA on the surface on Escherichia coli does not increase bacterial-monocyte association, but a NadA-positive strain induced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 26 publications
5
39
0
Order By: Relevance
“…By using soluble recombinant GFP-tagged CEACAMs and Y. enterocolitica expressing yadA or nadA and N. gonorrhoeae as controls we could demonstrate by flow cytometry that neither NadA nor YadA are recognized by CEACAM 1, 3, 5, 6, or 8, respectively. Previously it has been demonstrated that NadA induces chemokine IL-8 production of diverse host cell types similar to Yersinia Inv which is recognized by ␤1 integrins (14,(35)(36)(37). This prompted us to check whether NadA could also interact with ␤1 integrins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By using soluble recombinant GFP-tagged CEACAMs and Y. enterocolitica expressing yadA or nadA and N. gonorrhoeae as controls we could demonstrate by flow cytometry that neither NadA nor YadA are recognized by CEACAM 1, 3, 5, 6, or 8, respectively. Previously it has been demonstrated that NadA induces chemokine IL-8 production of diverse host cell types similar to Yersinia Inv which is recognized by ␤1 integrins (14,(35)(36)(37). This prompted us to check whether NadA could also interact with ␤1 integrins.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, antigen-presenting dendritic cells (DCs), macrophages and neutrophils, which have been recruited to bacterial entry sides, also express ␣4␤1 and/or ␣5␤1 integrins. In analogy to invasin-expressing Yersinia it is not unlikely that N. meningitidis interacts through NadA with ␣␤1 integrins of M-cells of the NALT and with DCs, macrophages and neutrophils of the submucosa (14,24,36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, NadA-specific receptors were observed also on monocytes, macrophages, and monocyte-derived dendritic cells (9,13). NadA may stimulate antimeningococcal defenses by augmenting the immune response of dendritic cells (self-adjuvant effect) and by increasing antigen presentation by macrophages engaged in antimicrobial activity (9,13,17).…”
mentioning
confidence: 99%
“…In vitro observations indicated that NadA may also be important in mucosal colonization by N. meningitidis B: (i) its expression in Escherichia coli enhances bacterial association with Chang epithelial cells (a human conjunctiva cell line widely used in meningococcal pathogenesis studies) (2); (ii) a NadA knockout mutant of N. meningitidis shows a partial, yet significant, decrease in cell adhesion and invasion compared to a wild-type strain, suggesting that NadA cooperates with other factors in mediating bacterium-cell interactions (2); (iii) a soluble recombinant form of NadA (NadA with a deletion of residues 351 to 405 [NadA ⌬351-405 ]), lacking the membrane anchor region, binds to specific receptor sites with an apparent affinity of 3 M on Chang cells (2,9).…”
mentioning
confidence: 99%